The Impact of Coworking Spaces on the Wellbeing of Parenting Mothers : A Case Study of Jahoda Coworking - Šrámková, Kateřina (2024)
This thesis explores the impact of coworking spaces on working mothers' well-being and work-life balance. It acknowledges the challenges mothers face in balancing career and family, particularly the lack of childcare options in Prague. The research investigates how coworking spaces, like Jahoda, can address these challenges by offering a flexible and supportive work environment. Through semi-structured interviews and ethnographic research at Jahoda, the study examines how working mothers perceive the impact of the coworking space on their well-being, work-life balance, and productivity. The core research questions focus on how Jahoda contributes to these aspects for working mothers. The space offers flexibility, on-site childcare, and community options so mothers can feel less lonely. This reduces stress, improves work-life balance, and increases well-being for working mothers.